Implications Of Academic Service On Student Performance - Isthifa Kemal (Edunesia: Jurnal Ilmiah Pendidikan, 2022)
This study aims to reveal: 1) student performance in the management education study program; 2) academic services carried out by the higher education management master's program at the University of North Sumatra; 3) whether there is an effect of educational services on student performance in the master's degree program in higher education management. The method used in this study is a survey method, namely by distributing questionnaires to respondents and describing respondents' answers qualitatively. Research Results: 1) Student performance of the UMSU Higher Education Management Masters Program, accustomed to being on time, taking notes from lecturers' explanations, actively preparing lecture materials, actively asking and answering questions, accustomed to making lecture summaries, filling out attendance lists, searching and reviewing source books, study groups, and participate in activities organized by the Study Program. 2) Administrative services have been carried out in an orderly and fair manner for 11 types of services, namely lecture scheduling, lecture preparation, lecture implementation, class determination, student grouping, lecture evaluation, thesis writing supervisor assignments, guidance process, implementation proposal seminars, thesis examination implementation, and student study completion process. All these services have been carried out satisfactorily and adequately. 3) There is a direct positive effect of administrative services on student performance in the higher education management study program. The results have significance for higher education. These findings can make academic service implications for student performance. Penelitian ini bertujuan untuk mengungkap: 1) kinerja mahasiswa pada program studi pendidikan manajemen; 2) pelayanan akademik yang dilaksanakan oleh program studi magister manajemen pendidikan tinggi Universitas Sumatera Utara; 3) apakah ada pengaruh pelayanan pendidikan terhadap kinerja mahasiswa pada program studi magister manajemen pendidikan tinggi. Metode yang digunakan dalam penelitian ini adalah metode survei, yaitu dengan menyebarkan kuesioner kepada responden dan mendeskripsikan jawaban responden secara kualitatif. Hasil Penelitian: 1) Kinerja mahasiswa Program Studi Magister Manajemen Pendidikan Tinggi UMSU, terbiasa hadir tepat waktu, mencatat penjelasan dosen, aktif menyiapkan materi perkuliahan, aktif bertanya dan menjawab pertanyaan, terbiasa membuat ringkasan kuliah, mengisi daftar hadir, mencari dan mereview buku sumber, belajar kelompok, dan mengikuti kegiatan yang diselenggarakan oleh Program Studi. 2) Pelayanan administrasi telah dilakukan secara tertib dan adil untuk 11 jenis pelayanan yaitu penjadwalan perkuliahan, persiapan perkuliahan, pelaksanaan perkuliahan, penentuan kelas, pengelompokan mahasiswa, evaluasi perkuliahan, tugas pembimbing penulisan skripsi, proses bimbingan, seminar proposal pelaksanaan, pelaksanaan ujian tesis, dan proses penyelesaian studi mahasiswa. Semua pelayanan tersebut telah dilaksanakan dengan memuaskan dan memadai. 3) Terdapat pengaruh langsung positif pelayanan administrasi terhadap kinerja mahasiswa pada program studi manajemen pendidikan tinggi. Hasilnya memiliki arti penting bagi pendidikan tinggi. Temuan ini dapat membuat implikasi layanan akademik untuk kinerja siswa